Pelatihan Pembuatan Video Sebagai Media Edukasi Pengelolaan Sampah - Ajy Waskyto Sugiyanto, Bagus; Zahra, Latifa (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
Garbage contains various toxic materials such as heavy metals, insecticides, and so on, so humans who come into direct contact with waste can be at risk of experiencing chronic digestive disorders. Members of the Demen Youth Organization will be involved in making Community Service Advertisements (PSAs) about waste disposal. PSAs are promotional media that gain public interest in the advertisements being promoted and are used as media for services and social organizations to be known as serving the wider community. And can give rise to new awareness that originates from individuals and groups. The implementation method for the service located in Demen Hamlet will be divided into three stages. The search technique will use observation and discussion methods with Karang Taruna to find message concepts.